Direct Intrahepatic Portosystemic Shunt in Budd-Chiari Syndrome: A Case Report and Review of the Literature - V. Chandra; E. Wajswol; M. Shahid; A. Kumar; S. Contractor (Case Reports in Radiology)
Transjugular intrahepatic portosystemic shunt (TIPS) is an alternative interventional procedure used to manage refractory Budd-Chiari syndrome (BCS) when conservative medical therapy has failed. However, TIPS is not always technically successful because of hepatic vein thrombosis and inability to catheterize the hepatic veins. In these situations, direct intrahepatic portosystemic shunt (DIPS) with access to the portal vein from the IVC has been shown to be a viable alternative that may ameliorate portal hypertension in these patients. Typically, DIPS involves the use of transabdominal ultrasound to target the portal vein. Herein a case in which a 39-year-old female underwent DIPS without the use of ultrasound guidance is presented. Instead, a hepatic venogram generated using collateral circulation was used to opacify and guide access to the portal vein.